PENGARUH INFLASI, SUKU BUNGA, DAN SOLVABILITAS TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2021-2023 - KADEK ALDI; Wahyuni, Made Arie (Vokasi : Jurnal Riset Akuntansi, 2024)
This study aims to determine the effect of inflation, interest rates, and solvency on company value in banking companies listed on the Indonesia Stock Exchange in 2021-2023. This research is quantitative research using secondary data. The sample in this study amounted to 138 companies. Data analysis techniques in this study include normality test, heteroscedasticity test, multicollinearity test, autocorrelation test, t test and determination coefficient test. The results of the study show that inflation has a negative and insignificant effect on company value, interest rates (BI Rate) have a negative and significant effect on company value, and solvency (DER) has a negative and significant effect on company value. In the coefficient of determination test, adjusted R square data results of 7.5% can be explained by inflation, interest rates, and solvency, while the remaining 92.5% can be explained by the influence of other variables that are not studied by the author.